2023
DOI: 10.1021/acsenergylett.3c00697
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the Interface-Driven Losses in Inverted Perovskite Solar Cells and Modules

Abstract: The inverted p-i-n perovskite solar cells hold high promise for scale-up toward commercialization. However, the interfaces between the perovskite and the charge transport layers contribute to major power conversion efficiency (PCE) loss and instability. Here, we use a single material of 2-thiopheneethylammonium chloride (TEACl) to molecularly engineer both the interface between the perovskite and fullerene-C 60 electron transport layer and the buried interface between the perovskite and NiO x -based hole trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Reproduced with permission. 91 Copyright 2023, American Chemical Society. (g) Schematic illustration of suppressing perovskite decomposition by LS1.…”
Section: Interfacial Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. 91 Copyright 2023, American Chemical Society. (g) Schematic illustration of suppressing perovskite decomposition by LS1.…”
Section: Interfacial Modificationmentioning
confidence: 99%
“…7f ). 91 The TEACl-based dual interfaces contribute to the optimal band alignment and reduced defect sites, and improve interfacial contact, resulting in a high photovoltaic performance. The TEACl dual-treated PSC exhibits a PCE of 22.6% for the large submodule with an active area of 3.63 cm 2 .…”
Section: Interfacial Modificationmentioning
confidence: 99%
“…In spite of the good performance achieved in air-processed FAPbI 3 PSCs, these strategies were mostly applied in the devices with regular (n-i-p) structure. In contrast, inverted (p-i-n) FAPbI 3 PSCs have been rarely constructed in ambient air even though they show advantages such as low-temperature preparation process of electron transport materials, dopant-free hole transport materials, etc. , Our prior work demonstrated a strategy for fabricating inverted FAPbI 3 PSCs in a humid environment by introducing phenylethylammonium iodide (PEAI) . However, the efficiency obtained for inverted FAPbI 3 PSCs fabricated in ambient air still lags far behind that of the regular one.…”
Section: Introductionmentioning
confidence: 99%
“…Organic molecules or self-assembled monolayers (SAMs) have been used to improve the surface chemistry, stabilize the NiO x /perovskite interface, and modify the work function (WF) of NiO x . [19][20][21] Prior studies showed that the functional groups of SAMs can be engineered to modify the surface and interfacial properties like wetting [22] and to control the WF of the metal oxide surfaces for better energy-level alignment [23,24] to improve performance of PSCs. In the last years, carbazole-based SAMs with the phosphonic acid anchoring ), and used them as a standalone HTL in singlejunction PSCs, as well as in the tandem configurations.…”
Section: Introductionmentioning
confidence: 99%